Higher Education Reform in Vietnam: Current Situation, Challenges and Solutions - Nguyễn, Nhã Văn; Vũ, Tú Ngọc (VNU Journal of Science: Social Sciences and Humanities; Vol 31 No 4, 2015)
The comprehensive reform that has been vigorously carried out over the last decades in all sectors has achieved important results. In spite of many difficulties and challenges, “Vietnam’s GDP growth rates have been very strong compared to its South-East Asian neighbors” (Nuffic Neso Vietnam). That has been attributed to higher education reform as higher education has been considered a very important part of the renewal of the State. In other words, Vietnam’s higher education reform that has been carried out since the late 90’s of the last century has recorded remarkable achievements. Firstly, the university scope and network has better met the people’s learning requirements. Secondly, higher education quality has been gradually enhanced. Thirdly, equity of accessing higher education has been improved. Fourthly, university governance has changed for the better. Fifthly, teaching and administrative staff have considerably increased in terms of quality and quantity. Sixthly, private higher education has developed. Seventhly, investment in higher education has increased and lastly, higher education institutions’ physical facilities have improved (Education Development Strategy 2011-2012, June, 2012). However, there are still a number of issues to be solved chiefly in the training area in such a way that makes the higher education reform achieve its aims: (i) to produce human resources, raise people’s intellectual level, foster talent, conduct R&D in order to generate knowledge, create new products to meet the requirements of socio-economic development, national defense, security and international integration and (ii) to upgrade some universities to international standards and improve the competitive strength of the country’s human resources and economy (Higher Education Law, 2012). Key words: higher education, reform, objectives, challenges, solutions